2002
DOI: 10.1029/2001jd000777
|View full text |Cite
|
Sign up to set email alerts
|

Pointing and temperature retrieval from millimeter‐submillimeter limb soundings

Abstract: [1] Passive microwave limb sounding instruments like the Millimeter-Wave Atmospheric Sounder (MAS) or the Microwave Limb Sounder (MLS) observe dedicated oxygen lines for the derivation of temperature and pointing information, since these quantities are essential for the quality of the retrieval of the trace gas mixing ratio. Emission lines of oxygen are chosen because the volume mixing ratio (VMR) profile is known. In this paper, we demonstrate the capabilities of a new and innovative method by means of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…A root‐mean square retrieval error was then determined from the individually determined retrieval errors. See, for example, Urban [2003] and Verdes et al [2002] for a more detailed discussion of this method and Urban et al [2004a] for a definition of the contribution functions in MOLIERE‐5.…”
Section: Systematic Errorsmentioning
confidence: 99%
“…A root‐mean square retrieval error was then determined from the individually determined retrieval errors. See, for example, Urban [2003] and Verdes et al [2002] for a more detailed discussion of this method and Urban et al [2004a] for a definition of the contribution functions in MOLIERE‐5.…”
Section: Systematic Errorsmentioning
confidence: 99%
“…Retrieved was the volume mixing ratio (VMR) in relative units, that is, x = VMR true /VMR reference , and the temperature in absolute units (Kelvin), as described in detail by Verdes et al [2002]. The reference VMR profiles are the ones shown in Figure 2.…”
Section: Retrieval Simulationsmentioning
confidence: 99%
“…The relevant pointing information was provided by the Attitude and Heading Reference System (AHRS) [16] and its uncertainty is within 1 arcmin. It has been suggested that the pointing information can be derived from measurements of oxygen emission lines [54][55][56][57][58]. However, due to the very high noise temperature in the TELIS O 2 microwindow, an accurate retrieval of the pointing information is not feasible; further, it is not required because of the high quality of the AHRS data.…”
Section: Instrumentmentioning
confidence: 99%
“…Consequently, the TELIS consortium did not define any dedicated ozone microwindow during these three campaigns. To choose a proper ozone line for the retrieval, one should take into account the energy of the lower state where the transition occurs since this quantity reflects the expected sensitivity to atmospheric temperature [57].…”
Section: Limb Spectramentioning
confidence: 99%